Role of brand personality and consumer brand identification on hypermarket brand evaluation and loyalty development among Malaysian customers - Nikhashemi, Seyed Rajab (2015)
In Malaysia, the robust economic growth in the late 1980s and early 1990s has resulted rapid expansion of foreign and local hypermarkets. In line with this trend, Malaysia has experienced a massive increase in brand-conscious customers who demand greater product varieties and qualities, posing challenges to the quality of the hypermarkets. Therefore,building customer brand loyalty through branding strategies, as weapons to secure a competitive edge in the hypermarket industry, has gathered momentum among researchers. Both firms and customers can enjoy considerable advantages in terms of a strong customer brand loyalty. A strong hypermarket brand enhances the market value of a property, financial performance, and other key performance indicators, such as revenue, return on investment,and average price. On the other hand, a strong hypermarket brand reduces customers’perceived risks and search costs, provides a good indicator of quality assurance, and simplifies customers’ pre-purchase assessment of the experience. Paying attention to the factors which play major roles in building and maintaining customer brand loyalty is essential for consumer science and brand managers. In this study, a structural model of customer brand loyalty was developed to investigate the relationships among brand personality, customer brand identification, and some selected mediating variables, including customer perceived service quality, perceived value, brand trust, brand commitment and positive word-of-mouth communication towards building customer brand loyalty among Malaysian hypermarket customers. The theories of selfcongruity,anthropomorphic, mean end, social identity and cognitive approach among others,best accentuates the important roles of the mentioned variables in customer brand loyalty. These theories build up the theoretical foundation of this research’s conceptual model. In this study, self-administered questionnaires through convenience sampling were distributed among 460 Malaysian hypermarket customers of four selected Klang Valley hypermarkets, i.e. Mydin, Giant, Tesco and Aeon Big. Descriptive, exploratory and confirmatory factor analyses were run to analyze the data. Besides, structure equation modeling with 381 respondents was conducted to examine the hypothesized relationships among the constructs as postulated in the proposed model. The results of EFA revealed that sincerity, followed by sophistication and competence were the most significant dimensions to predict brand personality in Malaysian hypermarket industry. The results of the hypothesized structural model also showed the indirect relationship between brand personality (BP) and customer brand loyalty (CBL) through mediating customer brand identification (CBI). Moreover, CBI partially- through mediating perceive service quality (PSQ), perceive value (PV), brand trust (BT), brand commitment (BCOMM), and positive word-of-mouth communication (WOMC) associated with customer brand loyalty. Interestingly, among the aforementioned mediating variables, BCOMM and WOMC showed the highest direct impacts on customer brand loyalty. Finally, testing a rival model proposed that customer brand loyalty will be formed by the amalgamation of the indispensable aforementioned antecedents. While the significance of brand personality on the prediction of customer brand identification and customer brand loyalty had not been empirically scrutinized by the past studies, the current study provides findings which are essentially complementary to those studies. The findings of this study recommend that in building and maintaining customer brand loyalty, brand managers and consumer science researchers should pay closer attention to the indispensable roles of proposed brand loyalty antecedents, especially brand personality and customer brand identification. Finally, it is hoped that the findings of this study would help local hypermarket policy makers facilitate building customer brand loyalty in facing immense competition with foreign hypermarkets.